Stress within Families of Patients with Psychotic Disorders: Initial Study - Lida Nurlainah; Imas Rafiyah; Indra Maulana (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
Psychotic disorders are the most severe form of mental illness. The family is the primary supporter of patients with psychosis; as such, the family is likely to experience stress when caring for psychotic patients and assisting in their recovery. Data analysis regarding stress within families could inform the types of support that family members receive. This study aimed to determine stress within families of psychotic patients in Garut, Indonesia. A descriptive study was carried out using a quantitative approach. The samples collected were of the families who visited an outpatient clinic in Garut. A purposive sample of 70 respondents using the Slovin formula (10%) was recruited. Data were collected using the 42 Depression Anxiety Stress Scale (DASS) questionnaire, and univariate analysis was conducted. Results showed that 5.7% of the respondents experienced medium stress, 54.4% experienced mild stress, 41.4% did not experience stress, and only one person (1.4%) experienced severe stress. The findings suggest that families with psychotic patient experience stress. Further research is recommended to examine the factors and levels of stress within families of long-term acute psychotic patients. Abstrak Stres dalam Keluarga Pasien dengan Gangguan Psikotik. Gangguan psikotik adalah bentuk penyakit mental yang paling parah. Keluarga adalah pendukung utama pasien yang menderita psikosis,keluarga cenderung mengalami stres ketika merawat pasien psikotik dan membantu dalam pemulihan mereka. Analisis data mengenai stres keluarga dapat menginformasikan jenis dukungan yang diterima anggota keluarga. Tujuan dari penelitian ini adalah untuk mengetahui stres keluarga dengan pasien psikotik di Garut, Indonesia. Studi deskriptif dilakukan dengan menggunakan pendekatan kuantitatif. Sampel yang dikumpulkan adalah dari keluarga yang mengunjungi klinik rawat jalan di daerah Garut. Sampel purposive dari 70 responden menggunakan rumus Slovin (10%) yang direkrut. Data dikumpulkan menggunakan kuesioner 42 Depression Anxietystress Scale (DASS) dengan melakukan analisis univariat. Hasil penelitian menunjukkan bahwa 5,7% responden mengalami stres sedang, 54,4% mengalami stres ringan, 41,4% tidak mengalami stres, dan hanya satu orang (1,4%) mengalami stres berat. Dapat disimpulkan dari temuan bahwa keluarga dengan pasien psikotikmengalami beberapa bentuk stres. Penelitian lebih lanjut direkomendasikan untuk memeriksa faktor-faktor dan tingkat stres keluarga dengan pasien psikotik akut lama. Kata Kunci: keluarga, psikotik, stres